Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1063/1.3359704
|View full text |Cite
|
Sign up to set email alerts
|

Deep levels in GaAs(001)/InAs/InGaAs/GaAs self-assembled quantum dot structures and their effect on quantum dot devices

Abstract: Currently lattice mismatch strain-driven three-dimensional coherent island based quantum dots, dubbed self-assembled quantum dots (SAQDs), constitute the most developed class of quantum dots with successful applications to lasers and considerable potential for infrared detectors in the 1–12 μm regime. This is in no small part a consequence of the extensive studies on the formation and control of the islands and on their capping by appropriate overlayer materials under optimal growth conditions. By contrast, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 44 publications
4
20
0
3
Order By: Relevance
“…This EL2-like defect has been previously seen by other groups in samples containing InAs QDs [13,18,19]. Asano et al has shown that this defect may be due in part to the low temperature GaAs capping layer, used to stabilize the InAs surface before a temperature ramp, rather than the QD itself [19]. Since QD-EL2 it is near the midgap and has a density in the 10 14 cm -3 range, it would likely be an effective majority or minority carrier trap, and thus could have a larger influence on minority carrier device properties (e.g.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This EL2-like defect has been previously seen by other groups in samples containing InAs QDs [13,18,19]. Asano et al has shown that this defect may be due in part to the low temperature GaAs capping layer, used to stabilize the InAs surface before a temperature ramp, rather than the QD itself [19]. Since QD-EL2 it is near the midgap and has a density in the 10 14 cm -3 range, it would likely be an effective majority or minority carrier trap, and thus could have a larger influence on minority carrier device properties (e.g.…”
Section: Discussionsupporting
confidence: 78%
“…The QD-EL2 defect has a relatively large capture cross-section (suggesting a complex defect similar to EL2), is near the mid- gap, and has a relatively high defect density. This EL2-like defect has been previously seen by other groups in samples containing InAs QDs [13,18,19]. Asano et al has shown that this defect may be due in part to the low temperature GaAs capping layer, used to stabilize the InAs surface before a temperature ramp, rather than the QD itself [19].…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, E2 PIN and E3 QWR have comparable activation energies as trap F (0.14 eV) reported by Asano et al [48] in GaAs (001) /InAs/InGaAs/GaAs self-assembled QD structures. In their study, they inferred that the increase of the density of this trap and others traps around the QDs is due to the growth conditions of InGaAs/GaAs QD structures.…”
Section: Dlts and Laplace Dlts Characteristicssupporting
confidence: 75%
“…Considering the data about intrinsic and crystal defects in In(Ga)As/GaAs heterostructures obtained from deep level transient spectroscopy, 23,24 PC spectroscopy, and thermally stimulated current, 16,17,25 we attribute the onset of the absorption spectrum at 0.68 eV to a transition from a EL2 defect center in the InGaAs/GaAs layer where defect concentration is high. 26,27 It is known that in semi-insulating GaAs, the level of EL2 center is located near 0.75 eV below the conduction band, 28 but in strained InGaAs the energy of transition involving EL2 defect states is reduced.…”
Section: Discussionmentioning
confidence: 99%